The Italian effort toward a coordinated observation of Essential Variables (EOV, ECV, EBV) in European Marine Environments. Long-term observation in the central Mediterranean seas and Italian coasts - Simone Toller; Emilio Urbinati; Debora Bellafiore; Caterina Bergami; Francesca De Pascalis; Marcello G. Magaldi; Marco Bellacicco; Federico Bellati; Maristella Berta; Angelo Boccacci; Roberto Bozzano; Fabio Brunetti; et al. (Frontiers in Marine Science, 2026)
Monitoring Essential Ocean, Climate, and Biodiversity Variables (EOVs, ECVs and EBVs) collected through the marine Research Infrastructures (RIs) is critical for assessing environmental status, improving scientific knowledge and defining environmental policies. This study evaluates the capacity of the Italian marine monitoring system, including facilities such as fixed stations, buoys, autonomous platforms, and mobile systems across the Mediterranean Sea, to produce those variables. Conducted in 2023 within the framework of the ITINERIS project ( https://itineris.cnr.it/ ), which aims to strengthen coordination among national and ESFRI RIs (European Strategy Forum on Research Infrastructures), the analysis systematically examines the spatial, thematic, and technological coverage of EOVs, ECVs, EBVs observations and their alignment with international standards for environmental monitoring of 155 facilities from eight Italian and pan-European marine RIs. Of the 107 EVs recognized, 50% were actively produced by the RIs considered, with over 90% meeting the established requirements for EVs. These numbers will be updated to reflect the new equipment acquired during the project’s implementation up to early 2026, which is expected to boost EVs production by approximately 38-40%. The national monitoring network demonstrates a high degree of maturity for oceanic and climate variables, while biodiversity observations remain less represented, indicating the need for further technological innovation and automation. These findings emphasize the importance of enhancing coordination and harmonization among RIs to ensure balanced and interoperable monitoring. The study provides key recommendations to strengthen Italy’s capacity to contribute to the global characterization of EOVs, ECVs, and EBVs and to support evidence-based environmental assessments and the development of robust environmental management strategies at European level.

Avenues towards reconciling wild and managed bee proponents - Alexis L. Beaurepaire; Katja Hogendoorn; David Kleijn; Gard W. Otis; Simon G. Potts; Theresa L. Singer; Samuel Boff; Christian Pirk; Josef Settele; Robert J. Paxton; Nigel E. Raine; Simone Tosi; et al. (Trends in Ecology & Evolution, 2025)

Association of vitamin D and bisphenol A levels with cardiovascular risk in an elderly Italian population: results from the InCHIANTI study - Maria Luisa Brandi; Francesca Marini; Simone Parri; Stefania Bandinelli; Teresa Iantomasi; Francesca Giusti; Eleonora Talluri; Giovanna Sini; Fabrizio Nannipieri; Santina Battaglia; Giovanni Tripepi; Colin Gerard Egan; et al. (GeroScience, 2024)
Few studies have evaluated the association between circulating levels of 25-hydroxyvitamin D (25(OH)D), 1,25-dihydroxyvitamin D (1,25(OH) 2 D), and the endocrine disruptor bisphenol A (BPA), with risk of cardiovascular (CV) disease in elderly individuals. This was a cross-sectional study in a subgroup of elderly people from the InCHIANTI Biobank in Italy. We examined the association between circulating serum vitamin D metabolites, 1,25(OH) 2 D, 25(OH)D, and the endocrine disrupting agent BPA, with an arbitrary CV risk score and the European Society of Cardiology-based 10-year CV risk (SCORE2/SCORE2-OP) using univariate and multiple regression. In 299 individuals, blood samples were tested for serum values of 25(OH)D, 1,25(OH) 2 D and urinary BPA levels. One hundred eighty individuals (60.2%) were deficient (< 20 ng/ml) in 25(OH)D. Levels of 25(OH)D and 1,25(OH) 2 D were negatively correlated with CV risk score ( p < 0.0001 for both) as well as SCORE2/SCORE2-OP ( p < 0.0001 for both) while BPA levels were positively correlated with both CV risk scores ( p < 0.0001 for both). In a logistic regression model, male gender (odds ratio; OR: 2.1, 95% CI:1.1–3.8, p = 0.022), obesity (OR:2.8, 95% CI:1.2–6.5, p = 0.016) and BPA levels ≥ 110 ng/dl (OR:20.9, 95% CI:9.4–46.8, p < 0.0001) were associated with deficient levels of 25(OH)D. 1,25(OH)2D levels < 41 ng/dl and 25(OH)D levels < 20 ng/ml were associated with CV risk score ≥ 3 (OR: 4.16, 95% CI: 2.32–7.4, p < 0.0001 and OR: 1.86, 95% CI: 1.02–3.39, p = 0.044) respectively and 1,25(OH)2D levels < 41 ng/dl were associated with SCORE2/SCORE2-OP of ≥ 20% (OR:2.98, 95% CI: 1.7–5.2, p = 0.0001). In this cross-sectional analysis, BPA exposure was associated with significantly reduced levels of vitamin D that in turn were significantly associated with increased CV risk.

Seismic design spectra considering nonlinear connections between the existing building and the retrofit system - Simone Labò; Andrea Belleri; Alessandra Marini (Engineering Structures, 2024)

Seasonal dynamics of the microbiome-host response to pharmaceuticals and pesticides in Mytilus galloprovincialis farmed in the Northwestern Adriatic Sea - Giorgia Palladino; Simone Rampelli; Daniel Scicchitano; Enrico Nanetti; Letizia Iuffrida; Rajapaksha Haddokara Gedara Rasika Wathsala; Nicolò Interino; Mauro Marini; Emanuele Porru; Silvia Turroni; Jessica Fiori; Silvia Franzellitti; et al. (Science of The Total Environment, 2023)

Pin-supported walls as seismic retrofit for existing RC frames: performance improvement through link removal - Elena Casprini; Andrea Belleri; Alessandra Marini; Chiara Passoni; Simone Labò (Bulletin of Earthquake Engineering, 2023)
Pin-supported (PS) walls represent a possible solution for the seismic retrofit of existing reinforced concrete (RC) buildings, enabling linearization of the frame deformation along its height and consequently inhibiting soft storey collapse mechanisms. The effectiveness of this rehabilitation technology is strongly related to the characteristics of the existing frames, especially to the vertical distribution of the frame storey lateral stiffness. Since a larger 1st storey lateral stiffness may lead to a detrimental structural response of the retrofitted system, an alternative solution obtained from removing the connecting link between the 1st floor of the existing building and the pin-supported wall is investigated in this paper. An analytical method is proposed to derive the distribution of the internal actions in a dual 2D RC frame-PS wall system without the link at the 1st floor level, considering both a linear and nonlinear behaviour of the frame. It emerges that some parameters describing the structure type can provide straightforward information on the suitability of this solution in the seismic retrofit of existing RC buildings. As a result, a simplified procedure has been derived to preliminarily define the retrofit system configuration and evaluate the maximum demand in the PS wall. Such a procedure is finally applied with reference to a frame representing a RC building and finite element model analyses are carried out for validation purposes.

Loss of support assessment for precast portal frames with friction connections and masonry infills - Simone Labò; Marius Eteme Minkada; Alessandra Marini; Andrea Belleri (Bulletin of Earthquake Engineering, 2022)
The loss of support of beam elements in Italian precast buildings is one of the main vulnerabilities recorded in past earthquakes. The reason for beam falling is due to the absence of adequate structural details in the beam-column joints, which were typically relying on friction for buildings located in regions previously classified as non-seismic prone. To guarantee the structural safety of the whole existing building stock, this collapse mechanism must be further investigated; in this regard, it could be interesting to evaluate the level of safety achieved by simple beam-column friction connections to allow, for instance, the prioritization of the retrofit interventions to guarantee a minimum level of safety in a wide range of structures. The paper investigates the influence of the parameters governing the beam-column relative displacements in the case of friction connections to establish criteria for evaluating the seismic loss of support probability in existing precast buildings. A simplified analytical model is introduced to describe single and double portal frames with and without the presence of stiff masonry infills. The influence of the epicentral distance on the results obtained is also preliminary addressed. Nonlinear time history analyses are carried out on a 2D finite element model to validate the effectiveness of the simplified model taking as reference a building that experienced the loss of support of a main beam during a past earthquake.

Advancing fishery-independent stock assessments for the Norway lobster (Nephrops norvegicus) with new monitoring technologies - Jacopo Aguzzi; Damianos Chatzievangelou; Nathan J. Robinson; Nixon Bahamon; Alan Berry; Marc Carreras; Joan Batista Company; Corrado Costa; Joaquin del Rio Fernandez; Ahmad Falahzadeh; Spyros Fifas; Sascha Flögel; et al. (Frontiers in Marine Science, 2022)
The Norway lobster, Nephrops norvegicus , supports a key European fishery. Stock assessments for this species are mostly based on trawling and UnderWater TeleVision (UWTV) surveys. However, N. norvegicus are burrowing organisms and these survey methods are unable to sample or observe individuals in their burrows. To account for this, UWTV surveys generally assume that “1 burrow system = 1 animal”, due to the territorial behavior of N. norvegicus . Nevertheless, this assumption still requires in-situ validation. Here, we outline how to improve the accuracy of current stock assessments for N. norvegicus with novel ecological monitoring technologies, including: robotic fixed and mobile camera-platforms, telemetry, environmental DNA (eDNA), and Artificial Intelligence (AI). First, we outline the present status and threat for overexploitation in N. norvegicus stocks. Then, we discuss how the burrowing behavior of N. norvegicus biases current stock assessment methods. We propose that state-of-the-art stationary and mobile robotic platforms endowed with innovative sensors and complemented with AI tools could be used to count both animals and burrows systems in-situ , as well as to provide key insights into burrowing behavior. Next, we illustrate how multiparametric monitoring can be incorporated into assessments of physiology and burrowing behavior. Finally, we develop a flowchart for the appropriate treatment of multiparametric biological and environmental data required to improve current stock assessment methods.

Machine learning applied to big data from marine cabled observatories: A case study of sablefish monitoring in the NE Pacific - Federico Bonofiglio; Fabio C. De Leo; Connor Yee; Damianos Chatzievangelou; Jacopo Aguzzi; Simone Marini (Frontiers in Marine Science, 2022)
Ocean observatories collect large volumes of video data, with some data archives now spanning well over a few decades, and bringing the challenges of analytical capacity beyond conventional processing tools. The analysis of such vast and complex datasets can only be achieved with appropriate machine learning and Artificial Intelligence (AI) tools. The implementation of AI monitoring programs for animal tracking and classification becomes necessary in the particular case of deep-sea cabled observatories, as those operated by Ocean Networks Canada (ONC), where Petabytes of data are now collected each and every year since their installation. Here, we present a machine-learning and computer vision automated pipeline to detect and count sablefish ( Anoplopoma fimbria ), a key commercially exploited species in the N-NE Pacific. We used 651 hours of video footage obtained from three long-term monitoring sites in the NEPTUNE cabled observatory, in Barkley Canyon, on the nearby slope, and at depths ranging from 420 to 985 m. Our proposed AI sablefish detection and classification pipeline was tested and validated for an initial 4.5 month period (Sep 18 2019-Jan 2 2020), and was a first step towards validation for future processing of the now decade-long video archives from Barkley Canyon. For the validation period, we trained a YOLO neural network on 2917 manually annotated frames containing sablefish images to obtain an automatic detector with a 92% Average Precision (AP) on 730 test images, and a 5-fold cross-validation AP of 93% (± 3.7%). We then ran the detector on all video material (i.e., 651 hours from a 4.5 month period), to automatically detect and annotate sablefish. We finally applied a tracking algorithm on detection results, to approximate counts of individual fishes moving on scene and obtain a time series of proxy sablefish abundance. Those proxy abundance estimates are among the first to be made using such a large volume of video data from deep-sea settings. We discuss our AI results for application on a decade-long video monitoring program, and particularly with potential for complementing fisheries management practices of a commercially important species.

Pin-supported walls as seismic retrofit for existing RC frames: feasibility and preliminary design - Elena Casprini; Andrea Belleri; Alessandra Marini; Simone Labò; Chiara Passoni (Bulletin of Earthquake Engineering, 2022)
The seismic retrofit of the existing building heritage represents an urgent issue to be faced and innovative solutions which allow to overcome renovation barriers are needed. In this scenario, pin-supported (PS) walls represent an eligible solution, enabling linearization of the deformation of the frame along its height and inhibiting soft storey collapse mechanisms. The PS wall can be connected to the existing building from outside, thereby avoiding disruption to occupants or their relocation, which are acknowledged as the main barriers to the renovation nowadays. Suitability of PS wall solutions in the seismic retrofit of the existing building stock has been investigated herein, particularly in the case of existing reinforced concrete (RC) buildings, preliminarily focusing on 2D RC frames. The paper shows the weaknesses and strengths of the PS wall solution in relation to the specific features of the considered buildings. An analytical closed-form formulation is proposed and applied as a preliminary tool to evaluate the load distribution in the existing frame and in the PS wall after the retrofit considering the first mode of vibration of the retrofitted system. The results show that, in some conditions, the application of PS walls may be detrimental to the structural response. Along with the evaluation of the effectiveness of the retrofit solution, the proposed formulation allows a preliminary design of the retrofit system. Finally, a series of finite element model analyses have been carried out for validation purposes showing a good agreement between the proposed analytical formulation and the numerical results.

The colors of our brain: an integrated approach for dimensionality reduction and explainability in fMRI through color coding (i-ECO) - Livio Tarchi; Stefano Damiani; Paolo La Torraca Vittori; Simone Marini; Nelson Nazzicari; Giovanni Castellini; Tiziana Pisano; Pierluigi Politi; Valdo Ricca (Brain Imaging and Behavior, 2022)
Several systematic reviews have highlighted the role of multiple sources in the investigation of psychiatric illness. For what concerns fMRI, the focus of recent literature preferentially lies on three lines of research, namely: functional connectivity, network analysis and spectral analysis. Data was gathered from the UCLA Consortium for Neuropsychiatric Phenomics. The sample was composed by 130 neurotypicals, 50 participants diagnosed with Schizophrenia, 49 with Bipolar disorder and 43 with ADHD. Single fMRI scans were reduced in their dimensionality by a novel method (i-ECO) averaging results per Region of Interest and through an additive color method (RGB): local connectivity values (Regional Homogeneity), network centrality measures (Eigenvector Centrality), spectral dimensions (fractional Amplitude of Low-Frequency Fluctuations). Average images per diagnostic group were plotted and described. The discriminative power of this novel method for visualizing and analyzing fMRI results in an integrative manner was explored through the usage of convolutional neural networks. The new methodology of i-ECO showed between-groups differences that could be easily appreciated by the human eye. The precision-recall Area Under the Curve (PR-AUC) of our models was > 84.5% for each diagnostic group as evaluated on the test-set – 80/20 split. In conclusion, this study provides evidence for an integrative and easy-to-understand approach in the analysis and visualization of fMRI results. A high discriminative power for psychiatric conditions was reached. This proof-of-work study may serve to investigate further developments over more extensive datasets covering a wider range of psychiatric diagnoses.

Artificial Intelligence in Marine Science and Engineering - Fausto Pedro García Márquez; Mayorkinos Papaelias; Simone Marini (Journal of Marine Science and Engineering, 2022)
This Special Issue covers research in Artificial Intelligence in Marine Science and Engineering and shows how to apply it to many different professional areas, e [...]

Assessing the Image Concept Drift at the OBSEA Coastal Underwater Cabled Observatory - Ennio Ottaviani; Marco Francescangeli; Nikolla Gjeci; Joaquin del Rio Fernandez; Jacopo Aguzzi; Simone Marini (Frontiers in Marine Science, 2022)
The marine science community is engaged in the exploration and monitoring of biodiversity dynamics, with a special interest for understanding the ecosystem functioning and for tracking the growing anthropogenic impacts. The accurate monitoring of marine ecosystems requires the development of innovative and effective technological solutions to allow a remote and continuous collection of data. Cabled fixed observatories, equipped with camera systems and multiparametric sensors, allow for a non-invasive acquisition of valuable datasets, at a high-frequency rate and for periods extended in time. When large collections of visual data are acquired, the implementation of automated intelligent services is mandatory to automatically extract the relevant biological information from the gathered data. Nevertheless, the automated detection and classification of streamed visual data suffer from the “concept drift” phenomenon, consisting of a drop of performance over the time, mainly caused by the dynamic variation of the acquisition conditions. This work quantifies the degradation of the fish detection and classification performance on an image dataset acquired at the OBSEA cabled video-observatory over a one-year period and finally discusses the methodological solutions needed to implement an effective automated classification service operating in real time.

Framing Cutting-Edge Integrative Deep-Sea Biodiversity Monitoring via Environmental DNA and Optoacoustic Augmented Infrastructures - Sergio Stefanni; Luca Mirimin; David Stanković; Damianos Chatzievangelou; Lucia Bongiorni; Simone Marini; Maria Vittoria Modica; Elisabetta Manea; Federico Bonofiglio; Joaquin del Rio Fernandez; Neven Cukrov; Ana Gavrilović; et al. (Frontiers in Marine Science, 2022)
Deep-sea ecosystems are reservoirs of biodiversity that are largely unexplored, but their exploration and biodiscovery are becoming a reality thanks to biotechnological advances (e.g., omics technologies) and their integration in an expanding network of marine infrastructures for the exploration of the seas, such as cabled observatories. While still in its infancy, the application of environmental DNA (eDNA) metabarcoding approaches is revolutionizing marine biodiversity monitoring capability. Indeed, the analysis of eDNA in conjunction with the collection of multidisciplinary optoacoustic and environmental data, can provide a more comprehensive monitoring of deep-sea biodiversity. Here, we describe the potential for acquiring eDNA as a core component for the expanding ecological monitoring capabilities through cabled observatories and their docked Internet Operated Vehicles (IOVs), such as crawlers. Furthermore, we provide a critical overview of four areas of development: (i) Integrating eDNA with optoacoustic imaging; (ii) Development of eDNA repositories and cross-linking with other biodiversity databases; (iii) Artificial Intelligence for eDNA analyses and integration with imaging data; and (iv) Benefits of eDNA augmented observatories for the conservation and sustainable management of deep-sea biodiversity. Finally, we discuss the technical limitations and recommendations for future eDNA monitoring of the deep-sea. It is hoped that this review will frame the future direction of an exciting journey of biodiscovery in remote and yet vulnerable areas of our planet, with the overall aim to understand deep-sea biodiversity and hence manage and protect vital marine resources.

Exploiting trap color to improve surveys of longhorn beetles - Giacomo Cavaletto; Massimo Faccoli; Lorenzo Marini; Johannes Spaethe; Filippo Giannone; Simone Moino; Davide Rassati (Journal of Pest Science, 2021)
Longhorn beetles are commonly moved among continents within wood packaging materials used in trades. Visual inspections carried out at points of entry often fail to detect exotic longhorn beetles as infested materials may have little or no sign of colonization. Black-colored traps baited with pheromones and host volatiles are thus used to improve chances of detection. Here we tested whether existing surveillance protocols for longhorn beetles can be further improved using trap colors different than black. Baited traps of eight different colors (i.e., grey, yellow, green, red, blue, brown, purple and black) were deployed in a randomized complete block design at 16 sites in northern Italy in 2019. A total of 6,001 individuals from 56 longhorn beetle species were trapped. In general, yellow and blue traps caught a significantly higher number of longhorn beetle species than black traps. In addition, trap color significantly affected species richness and abundance at the subfamily and species level, with mixed response mostly linked to the habit of visiting flowers for food. Flower-visiting longhorn beetles mainly exhibited clear preference for flower-related colors, i.e., yellow, green and blue, whereas non-flower-visiting species were more attracted by dark and long-wavelength-dominated colors, like red and brown. Our results clearly indicate that generic surveillance programs should not rely exclusively on black traps and that the use of more trap colors can strongly improve the chance of detecting native and exotic longhorn beetles potentially moved with trades.

Brain tissue transcriptomic analysis of SIV-infected macaques identifies several altered metabolic pathways linked to neuropathogenesis and poly (ADP-ribose) polymerases (PARPs) as potential therapeutic targets - Carla Mavian; Andrea S. Ramirez-Mata; James Jarad Dollar; David J. Nolan; Melanie Cash; Kevin White; Shannan N. Rich; Brittany Rife Magalis; Simone Marini; Mattia C. F. Prosperi; David Moraga Amador; Alberto Riva; et al. (Journal of NeuroVirology, 2021)
Despite improvements in antiretroviral therapy, human immunodeficiency virus type 1 (HIV-1)-associated neurocognitive disorders (HAND) remain prevalent in subjects undergoing therapy. HAND significantly affects individuals’ quality of life, as well as adherence to therapy, and, despite the increasing understanding of neuropathogenesis, no definitive diagnostic or prognostic marker has been identified. We investigated transcriptomic profiles in frontal cortex tissues of Simian immunodeficiency virus (SIV)-infected Rhesus macaques sacrificed at different stages of infection. Gene expression was compared among SIV-infected animals ( n = 11), with or without CD8+ lymphocyte depletion, based on detectable ( n = 6) or non-detectable ( n = 5) presence of the virus in frontal cortex tissues. Significant enrichment in activation of monocyte and macrophage cellular pathways was found in animals with detectable brain infection, independently from CD8+ lymphocyte depletion. In addition, transcripts of four poly (ADP-ribose) polymerases (PARPs) were up-regulated in the frontal cortex, which was confirmed by real-time polymerase chain reaction. Our results shed light on involvement of PARPs in SIV infection of the brain and their role in SIV-associated neurodegenerative processes. Inhibition of PARPs may provide an effective novel therapeutic target for HIV-related neuropathology.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

ENDURUNS: An Integrated and Flexible Approach for Seabed Survey Through Autonomous Mobile Vehicles - Simone Marini; Nikolla Gjeci; Shashank Govindaraj; Alexandru But; Benjamin Sportich; Ennio Ottaviani; Fausto Pedro García Márquez; Pedro Jose Bernalte Sanchez; Jonas Pedersen; Casper Vetke Clausen; Fantina Madricardo; Fedeirca Foglini; et al. (Journal of Marine Science and Engineering, 2020)
The oceans cover more than two-thirds of the planet, representing the vastest part of natural resources. Nevertheless, only a fraction of the ocean depths has been explored. Within this context, this article presents the H2020 ENDURUNS project that describes a novel scientific and technological approach for prolonged underwater autonomous operations of seabed survey activities, either in the deep ocean or in coastal areas. The proposed approach combines a hybrid Autonomous Underwater Vehicle capable of moving using either thrusters or as a sea glider, combined with an Unmanned Surface Vehicle equipped with satellite communication facilities for interaction with a land station. Both vehicles are equipped with energy packs that combine hydrogen fuel cells and Li-ion batteries to provide extended duration of the survey operations. The Unmanned Surface Vehicle employs photovoltaic panels to increase the autonomy of the vehicle. Since these missions generate a large amount of data, both vehicles are equipped with onboard Central Processing units capable of executing data analysis and compression algorithms for the semantic classification and transmission of the acquired data.

Global Deep-Sea Biodiversity Research Trends Highlighted by Science Mapping Approach - Corrado Costa; Emanuela Fanelli; Simone Marini; Roberto Danovaro; Jacopo Aguzzi (Frontiers in Marine Science, 2020)

Underwater photogrammetry in Antarctica: long-term observations in benthic ecosystems and legacy data rescue - Paola Piazza; Vonda Cummings; Alice Guzzi; Ian Hawes; Andrew Lohrer; Simone Marini; Peter Marriott; Fabio Menna; Erica Nocerino; Andrea Peirano; Sanghee Kim; Stefano Schiaparelli (Polar Biology, 2019)

Biodiversity conservation: an example of a multidisciplinary approach to marine dispersal - Stefano Aliani; Maristella Berta; Mireno Borghini; Daniel Carlson; Alessandra Conversi; Lorenzo Corgnati; Annalisa Griffa; Marcello Gatimu Magaldi; Carlo Mantovani; Simone Marini; Luca Mazzei; Giuseppe Suaria; et al. (Rendiconti Lincei. Scienze Fisiche e Naturali, 2015)

Coypu (Myocastor coypus) in a Mediterranean remnant wetland: a pilot study of a yearly cycle with management implications - Francesca Marini; Simone Ceccobelli; Corrado Battisti (Wetlands Ecology and Management, 2011)